The next generation of urban MACCs. Reassessing the cost-effectiveness of urban mitigation options by integrating a systemic approach and social costs. (May 2016) - Saujot, Mathieu; Lefèvre, Benoit
Abstract: Many cities are implementing policies and climate action plans. Yet local climate policies suffer from a lack of scientific understanding and evaluation methods able to support the definition of efficient mitigation strategies. The purpose of this paper is to build on classical approaches in the energy policy field that exist at the national and international level to propose an urban MACCs methodology able to fulfill this lack and inform local debates. The methodology is an extension of static "expert-based" MACCs; it combines a land use transport integrated model and an abatement cost methodology that integrates co-benefits, and takes into account the spatial and systemic dimensions of cities. The methodology is implemented for the transportation sector of a mid-sized European city (Grenoble, France). Our results present the cost-effectiveness and political feasibility of several proposed measures. We find that the inclusion of co-benefits can profoundly change the cost-benefit assessment of transport mitigation options. Moreover we underline the key parameters determining the cost-effectiveness ranking of mitigation options. These urban MACCs aim to serve as a bridge between urban planning and mitigation policies and can thus contribute to strengthen and align sustainable and climate change agendas at the local level. Highlights: Local climate policies lack scientific understanding for prioritizing mitigation actions. We develop a method to evaluate cost-effectiveness of urban transportation actions. This method combines urban modeling and MACCs to inform urban planning. Abatement costs from its application to a mid-sized city are presented. The impact of the inclusion of co-benefits is analyzed.